The efficient of beds used based on graphic Barber Johnson at Semen Padang Hospital in 2017 - Mandia, Sayati (International Journal Of Community Medicine And Public Health, 2019)
Background: Quality of hospital services can be seen from the bed usage. Statistical analysis of efficiency bed usage can be mesured based on inpatient medical records. To determine the efficiency requires four parameters namely bed occupancy rate (BOR), average length of stay (ALoS), turnover interval (TI), and bed turnover (BTR). parameters can be presented using Graphic Barber Johnson. This study aims to determine the efficiency of bed usage at Semen Padang Hospital in 2017. Methods: This research was conducted at Semen Padang Hospital, West Sumatera, Indonesia from January to December 2017. The study used a descriptive method with a qualitative approach. The data was collected from medical records department. The population is all abstraction data of in-patient medical record in 2017, 9796 medical record used total sampling technique. Data analysis was performed by calculating the values of ALoS, BOR, BTR, and TI. Data will be presented based on graphic Barber Johnson. Excel 2010 and graphic Barber Johnson method were applied for data analysis. Results: Number of daily inpatient censuses in 2017 are 31227 and number of service days are 31362. Number of beds 144. Statistical analysis results obtained total BOR 60%, BTR 67 times, TI 2 days and ALoS 3 days. The highest value of bed occupancy rate is 66% on August. Conclusions: Based on statistical, value of bed occupancy rate (60%) and turnover interval (2 days) are efficient at Semen Padang Hospital in 2017. Average length of stay (3 days) and bed turnover rate (67 times) are not efficient.